2022
DOI: 10.3390/plants11030318
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Volatile Organic Compounds Emitted by Two Beneficial Endophytic Pseudomonas Strains from Olive Roots

Abstract: The production of volatile organic compounds (VOCs) represents a promising strategy of plant-beneficial bacteria to control soil-borne phytopathogens. Pseudomonas sp. PICF6 and Pseudomonas simiae PICF7 are two indigenous inhabitants of olive roots displaying effective biological control against Verticillium dahliae. Additionally, strain PICF7 is able to promote the growth of barley and Arabidopsis thaliana, VOCs being involved in the growth of the latter species. In this study, the antagonistic capacity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
2
10
0
Order By: Relevance
“…Previous research has found that 1-undecene and squalene have antifungal and antinematode activities able to control soil-borne plant diseases. For instance, 1-undecene produced by P. chlororaphis and P. fluorescens have inhibitory activities on Colletotrichum dematium , C. gloeosporioides , Fusarium oxysporum , F. subglutinans and Stemphylium lycopersici in many plants, such as potato [ 34 ], maize [ 35 ], citrus [ 36 ], and olive [ 37 ]. In addition, squalene and 1-undecene can be used as a preservative for TCM and food/feed, because they have the ability to inhibit mold growth [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that 1-undecene and squalene have antifungal and antinematode activities able to control soil-borne plant diseases. For instance, 1-undecene produced by P. chlororaphis and P. fluorescens have inhibitory activities on Colletotrichum dematium , C. gloeosporioides , Fusarium oxysporum , F. subglutinans and Stemphylium lycopersici in many plants, such as potato [ 34 ], maize [ 35 ], citrus [ 36 ], and olive [ 37 ]. In addition, squalene and 1-undecene can be used as a preservative for TCM and food/feed, because they have the ability to inhibit mold growth [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…While they are not considered to be phytohormones per se, the volatile organic compounds (VOCs) that are synthesized by a wide range of soil bacteria have recently been shown to play a significant role in plant growth promotion [ 6 , 31 , 32 , 33 , 34 ]. The growth promotion effect of VOCs is largely attributed to the modulation of the synthesis and/or metabolism of known phytohormones, synthesized by either PGPB or by plants [ 35 , 36 ].…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%
“…However, in the study of plant growth-promoting functions of VOCs, VOCs cannot be used as the main criterion to evaluate the beneficial bacteria or that the VOCs of plant pathogens can also promote plant growth ( 33 ). The production of VOCs by Pseudomonas aeruginosa Picf7 isolated from olive root can promote the growth of barley and Arabidopsis thaliana ( 34 ), VOCs produced by Rhizoctonia solani can promote the growth of A. thaliana seedlings and adult seedlings ( 35 ), VOCs produced by Botrytis cinerea QT5-19 could promote the growth of tomato ( 36 ), and VOCs produced by Alternaria alternata promote the growth and flowering of A. thaliana ( 37 ). Although pathogens can also have VOCs that have plant growth-promoting functions, studies of VOC growth-promoting functions based on beneficial bacteria have broader application prospects and have become the focus of MVOC research ( 38 44 ).…”
Section: Introductionmentioning
confidence: 99%